The effects of different types of high-amylose maize starches on viscosity and digestion of acidified milk gels. (15th March 2023) - Li, Ruifen; Ding, Li; Guo, Ke; Qu, Jianzhou; Herburger, Klaus; Persson, Staffan; Blennow, Andreas; Zhong, Yuyue
Highlights: High-amylose maize starches (HAMSs) were used in casein and whey protein milk gels. HAMSs showed a greater effect on increasing viscosity of milk gels than normal starch. HAMSs showed a greater effect on increasing resistant starch content (RS) of milk gels. HAMSs had the highest viscosity in whey protein gel system than casein system. Hylon VII performed best on increasing viscosity and RS. Abstract: High-amylose maize starch (HAMS) can provide dietary fiber to foods. In this study, we investigated the effects of three HAMSs (Gelose 50, Hylon VII, and NAFU50) on the functionality of casein (CA) and/or whey protein (WP) networks in acidified milk gels using normal maize starch (NMS) as a control thickener. When compared with NMS, HAMSs performed better in increasing the resistant starch content (RS), storage modulus, loss modulus, and complex viscosity of all the milk gels. The results are attributed to the retention of the starch granular integrity of HAMSs during the preparation of the milk gels, as observed by microscopy. HylonVII exhibited the highest RS and viscosity in all milk gel systems, especially in WP gels (71.8 % RS and >3000 Pa.s at 1 Hz viscosity). Our data provide support for the potential of using HAMS to develop healthier yogurt products using functional thickeners from natural sources.